Coordinating a dual-channel supply chain with conditional value-at-risk under uncertainties of yield and demand. (January 2020) - Zhu, Baolin; Wen, Bin; Ji, Shoufeng; Qiu, Ruozhen
Highlights: The optimal model of CVaR is established for a dual-channel supply chain. The joint contract can achieve Pareto improvement for a dual-channel supply chain. The joint contract can improve the performance of a dual-channel supply chain. The experiments demonstrate the effectiveness of the model and the joint contract. Abstract: In a dual-channel supply chain, the coordination of retailer's risk-averse behavior is a challenging problem under uncertainties of manufacturing yield and market demand. This paper proposes a decision-making model in which Conditional Value-at-Risk (CVaR) criterion is used as the measure of risk assessment, analyzes the optimal decision in the centralized and decentralized situations respectively, and verifies that the joint contracts of revenue sharing contract and buyback contract can coordinate a dual-channel supply chain. The joint contracts proposed in this paper can achieve Pareto improvement for a dual-channel supply chain in which risk-averse retailer is involved under uncertainties of yield and demand. In experiments, this paper explores the effects of yield-demand uncertainty factor, risk-aversion factor and market distribution factor on the expected profits of manufacturer and CVaR value, and studies the feasible range of Pareto improvement in the joint contract model. The results show that the decision and profit of both the manufacturer and the retailer reply on the degree of the risk and uncertainty, and the possibility of the joint contract realizing the coordination becomes greater with the increase of the proportion of the channel's market share and, at the same time, the decrease of the risk-averse. In addition, the joint contract can coordinate the dual-channel supply chain, effectively improve the dual-channel supply chain performance, and achieve win-win goal for the dual-channel supply chain members.